2016
DOI: 10.1186/s12936-016-1405-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing supply-side barriers to uptake of intermittent preventive treatment for malaria in pregnancy: a qualitative study and document and record review in two regions of Uganda

Abstract: BackgroundIntermittent preventive treatment in pregnancy (IPTp) with sulfadoxine–pyrimethamine (SP), provided as part of routine antenatal care (ANC), is one of three malaria-in-pregnancy prevention and control mechanisms recommended by the World Health Organization (WHO). However, despite high ANC attendance and increased efforts to address known obstacles, IPTp uptake figures have remained low. This study aimed to identify and assess barriers that continue to impede IPTp uptake in Uganda, in particular for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 25 publications
12
68
1
Order By: Relevance
“…Though the sample size is not large enough to draw valid conclusions with regard to the accuracy of uptake figures, the research team’s difficulties in finding women who had not received a full course of IPTp may suggest higher than expected uptake compared with those reported through household surveys or HMIS. Data accuracy has been highlighted as a challenge to effective monitoring and evaluation of malaria interventions by the Government of Uganda [17], a conclusion which is also supported by supply-side findings from this study [12]. …”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…Though the sample size is not large enough to draw valid conclusions with regard to the accuracy of uptake figures, the research team’s difficulties in finding women who had not received a full course of IPTp may suggest higher than expected uptake compared with those reported through household surveys or HMIS. Data accuracy has been highlighted as a challenge to effective monitoring and evaluation of malaria interventions by the Government of Uganda [17], a conclusion which is also supported by supply-side findings from this study [12]. …”
Section: Methodssupporting
confidence: 77%
“…It also provides funds to PNFP facilities to procure essential medicines, including SP. However, this study found that stock-outs appear to persist in PNFP facilities [12]. Health workers at the PNFP facility included in the study sample indicated that they may charge women for the provision of IPTp or ask them to buy SP and bring it to the facility when they are experiencing stock-outs of the drug:

Researcher: Are women required to pay for the provision of IPTp at your facility?

…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the NMCP's report, out of all SPs procured, the only local pharmaceutical company supplied could supply only 16.20% making the program depend on international companies to supply remaining 83%. Considering the bureaucracy involved in importing drugs, the inability of local companies to respond to the demand of SPs results in low responsiveness especially during emergency stock-outs [23]. Also, the growing resistance of SP viz a viz non-existence of a medicinal alternative encourages low uptake especially in instances when resistance is reported [8].…”
Section: Product and Technologymentioning
confidence: 99%